Teknologi Imersif Virtual Reality untuk Neurorestorasi Anggota Gerak Atas Stroke - Gunawan, Hendry; Gunawan, Irene (Majalah Kedokteran Neurosains Perhimpunan Dokter Spesialis Saraf Indonesia, 2023)
ABSTRACT Stroke is leading cause of disability in Indonesia. Approximately 80% of stroke patients experience disabilities in their upper extremities. In recent years, immersive Virtual Reality (VR) technology has been used as a promising modality for neurorestoration. VR-based neurorestoration can induce neuroplasticity, Mirror-Neuron System (MNS) and Brain Reward System, leading to contrasted improvements in the upper extremity after stroke. This review prompts systematic understanding of the mechanisms of VR-based stroke neurorestoration and summarizes the emerging evidence for ongoing innovation of VR systems and application in stroke neurorestoration. Keywords: Virtual Reality, Neurorestoration, Stroke, Upper Extremity